2019
DOI: 10.1016/j.gexplo.2019.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Lateritic weathering of trachyte, and bauxite formation in West Cameroon: Morphological and geochemical evolution

Abstract: Bauxites and Fe laterites were formed on Neogene volcanics from Fongo-Tongo region in the highlands of western Cameroon, and are distributed on plateaus, slopes and downslope surfaces. Bauxitic profiles result from intense in-situ weathering of trachytes that implied depletion of silica and labile elements from the saprolite, while alumina relatively accumulated from parent minerals pseudomorphosis by primary gibbsite formation. During ongoing lateritization and bauxite maturation, important leaching and illuv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 50 publications
(47 reference statements)
0
10
0
Order By: Relevance
“…4a and Fig. 6), while SiO 2 with alkaline/alkaline-earth elements are depleted (see also Table DR2a , and Momo Nouazi et al, 2019). Noted that locally soils and upper parts of profiles formed also on trachyte from the same area (Tematio et al, 2009) may be more siliceous but less rich in Al 2 O 3 and/or Fe 2 O 3 than our samples (Fig.…”
Section: Lateritic Weathering On Trachytementioning
confidence: 54%
See 1 more Smart Citation
“…4a and Fig. 6), while SiO 2 with alkaline/alkaline-earth elements are depleted (see also Table DR2a , and Momo Nouazi et al, 2019). Noted that locally soils and upper parts of profiles formed also on trachyte from the same area (Tematio et al, 2009) may be more siliceous but less rich in Al 2 O 3 and/or Fe 2 O 3 than our samples (Fig.…”
Section: Lateritic Weathering On Trachytementioning
confidence: 54%
“…This requires continuous and efficient drainage to sustaining propagation of the weathering front into the bedrock (Braun et al, 2012;Prestrud Anderson et al, 2017, and references there-in). Weathering in profile on trachyte may have been enhanced by interconnected porosity (Momo Nouazi et al, 2019) that was formed by eluviation process of less cohesive clayey matrix (Fig. 5a).…”
Section: Constraints To Differentiated Bauxitic Weathering In Highlanmentioning
confidence: 99%
“…Then, at the intermediate layer the hardpans are made up of non-jointed blocks with fine gravels in-between them, and all these are located at altitudes between 1560 and 1580 m. These are often termed as sloped hardpans. Their discontinuous nature is generally attributed to in situ degeneration of initial hardpans [3,28,39]. At the lower layer these hardpans consist of fine gravels and are located at altitudes going from 1540 m to more than 1560 m. These fine gravels are breakdown products of the hardpans due to plant actions.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have reported mineral assemblages comprising goethite, hematite, aluminium hydroxides, kaolinite, and quartz, as well as the presence of Fe pisoids in lateritic palaeosols (e.g., Bauluz et al, 2014;Giovannini et al, 2017;Nkalih Mefire et al, 2018;Nouazi Momo et al, 2019;Yuste et al, 2017).…”
Section: Clay Minerals and Palaeoclimatementioning
confidence: 99%
“…In the uppermost Hauterivian-lower Barremian Torrelapaja Fm of the Torrelapaja subbasin (southeastern Cameros Basin), XRD and electron microscopy results show a higher content of kaolinite formed in-situ in the lower mudstone to calcareous mudstone levels, suggesting an intense chemical weathering characteristic of a warm and humid climate (Bauluz et al, 2014;Nouazi Momo et al, 2019;Raucskik & Varga, 2008;Won et al, 2018). As regards the pisoids and macropisoids, these would have been formed in environments of permanent groundwater saturation, which would have occurred in different episodes during the three sedimentary stages.…”
Section: Clay Minerals and Palaeoclimatementioning
confidence: 99%